FEATURES OF TECHNOLOGY OF WASHING AND DEVELOPMENT OF HORIZONTAL WELLS AFTER SELECTIVE HYDRAULIC FRACTURING OF LAYER ON FIELDS OF WESTERN SIBERIA - Alexander Evgenyevich Verisokin; Larisa Mikhaelovna Zinovieva (Наука. Инновации. Технологии)
Some features of washing technology and development after selective fracturing in Western Siberia. For greater efficiency fracturing operation necessary to carry out multi-stage hydraulic fracturing in horizontal wells. The analysis concluded that that involves tacitly adopted by the procedure of entering into operation of new wells in Western Siberia. The article describes the benefits of the multi-stage fracturing of conventional hydraulic fracturing. The technology of selective fracturing. The table shows the necessary equipment required for the operation with an indication of the minimum acceptable performance. Presents the advantages of the new technology in the time slot. Using the technology described washing and development of horizontal wells after fracturing selective not only significantly reduces the cycle time putting new wells into operation and the cycle of fracturing, but also reduces the risk of accidents in the wells and also reduces contamination layer zones.